The impact of engaging with community groups: asset-based approaches and the lived experience of socially vulnerable populations in the UK - Oonagh Corrigan; Suzanne Hughes; Scott Danielsen; Shannon Doherty; Russell Kabir (Frontiers Media S.A., 2023)
IntroductionAsset-based approaches to improve citizen wellbeing and address inequalities are now being adopted by public health practitioners. There is some evidence that participatory approaches and the promotion of community assets have the capacity to mitigate against the social determinants that generate health disparities. However, questions remain about how they work in practice. This paper reports on research carried out to provide insight into how a diverse range of community assets support (or not) the wellbeing of vulnerable citizens and to provide an improved understanding of people's lived experiences including the challenges of citizens who belong to community assets face. Two subsequent studies were undertaken in a region of England comprising of two neighboring municipalities where health inequalities are stark. Both municipalities contain within them areas of social deprivation. The initial study was completed in March 2020, 1 week before England's first COVID-19 lockdown restrictions were introduced and the subsequent study was conducted to explore the impact of social restrictions on the community assets forum members.MethodsA combined phenomenological and ethnographic methodological approach was adopted for both studies. For the initial study ethnographic methods were used including 42 qualitative face-to-face interviews focusing on the lived experience of participants. Observations, informal conversations, photographs, and field notes were also carried out to allow researchers to become familiar with the setting, to build rapport and trust provide a contextual understanding of the relationship between the activity or place and participants' experiences of wellbeing. For the subsequent study thirty-six interviews (including interviews with community assets leaders) were conducted online or by phone due to COVID-19 social restrictions.Results and discussionThe studies' findings support the supposition that these groups are community assets which help ameliorate against the social detriments of health and wellbeing that have led to widening health inequalities in the region. The findings from both studies clearly illustrate the importance of sociality for wellbeing, and that participation in these groups are an important determinant of wellbeing. The data demonstrates how social capital is generated within a range of community groups and spaces. It also conveys the needs and deficits existing within groups highlighting the need to provide more assistance to vulnerable citizens. While most themes were common to all community forums, there were some noticeable place-based differences.